2020
DOI: 10.1111/jerd.12664
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maxillary lateral incisor width ratio on perception of smile esthetics among orthodontists and laypersons

Abstract: Objective This study aimed to analyze the impact of different maxillary lateral incisor width ratios on the perception of smile esthetics among orthodontists and laypersons. Methods A smile photograph of a male subject showing the lips and gingival margins was selected. The smile was standardized for maxillary central incisor width proportions and ideally perceived smile esthetics. The maxillary lateral incisor width was symmetrically modified in increments of ratios of the central incisor from a ratio of 4:10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Regarding the participating population, only two studies grouped the population according to age (25–60 years [ 16 ] and a mean age of 25 years [ 49 ]), which is a relevant factor [ 54 ], as older groups of laypeople tolerate more discrepancies in smile esthetics than younger groups, except for gingival exposure >6 mm during the smile (considered nonesthetic by all age groups). By contrast, the influence of gender on the esthetic perception of smiles is considered insignificant in the literature [ 30 , 48 , 49 , 54 , 55 ]. In this study, most studies only briefly described the participant’s gender, while the others omitted the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the participating population, only two studies grouped the population according to age (25–60 years [ 16 ] and a mean age of 25 years [ 49 ]), which is a relevant factor [ 54 ], as older groups of laypeople tolerate more discrepancies in smile esthetics than younger groups, except for gingival exposure >6 mm during the smile (considered nonesthetic by all age groups). By contrast, the influence of gender on the esthetic perception of smiles is considered insignificant in the literature [ 30 , 48 , 49 , 54 , 55 ]. In this study, most studies only briefly described the participant’s gender, while the others omitted the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have evaluated the perception of smile esthetics by laypersons and dental professionals 12,24,37 . Most studies found that laypersons and dental professionals have different perceptions of smile esthetics 12,24 .…”
Section: Discussionmentioning
confidence: 99%
“…23,35,36 Numerous studies have evaluated the perception of smile esthetics by laypersons and dental professionals. 12,24,37 Most studies found that laypersons and dental professionals have different perceptions of smile esthetics. 12,24 Hence, clinicians may consider the OHR-QoL of their patients in determining the treatment goal to improve the therapeutic effect and to maximize patient satisfaction, instead of focusing too much on specific components of smile esthetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations